Malay identity in the exploration of miniature creation as souvenirs: contextual miniature of Malay architecture of North Sumatra, Indonesia - Zulkifli, Zulkifli; Kartono, Gamal; Misgiya, Misgiya; Kifli, Barli (Creativity Studies, 2024)
As a testament to the past Malay glory, there are monumental architectures in Medan (North Sumatra, Indonesia), Langkat (North Sumatra, Indonesia) and Batubara Regencies (North Sumatra, Indonesia) that have become Malay icons. The city of Medan and several areas in North Sumatra are known as tourist destinations since the early 20th century. The tourism has strong potential but it has not been supported by representative souvenir products. This article discusses the preservation of Malay identity through research into the manufacture of miniatures as souvenirs. The aim is to explore the potential of Malay architectural forms to be explored in the production of miniature souvenirs to revitalize North Sumatra’s Malay identity. The replicated research methods are survey, creation (creative experiment), and conservation methods in the socio-cultural approach. Research data was collected from various sources and analyzed using an interactive model. The results of the study explain that the potential identity of Malay architecture can be mapped based on its type (function) and structure. Its exploratory potential, both technically and aesthetically, lies in the dynamic visualization of roof forms and architectural facades. As it is researched based on the iconic Malay architectural figures, the miniature products are exclusive in the form of unique souvenirs with a strong Malay identity.